1995
DOI: 10.1038/bjc.1995.148
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of aberrant crypt foci in carcinogen-treated rats: association with intestinal carcinogenesis

Abstract: Summary Carcinogen-treated rats develop foci of aberrant crypts in the colon (ACFs) that have been interpreted as preneoplastic lesions. To characterise ACFs further, we studied in the unsectioned colon of rats the number, multiplicity, some morphological characteristics and the type of mucin production in ACFs. In ACFs observed 115 days after the administration of 50 mg kg-' 1,2-dimethylhydrazine (DMH), crypt multiplicity [number of aberrant crypts (AC) per focus] was positively correlated (P<0.0001) with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 13 publications
3
50
0
Order By: Relevance
“…37 The localization of b-catenin was also determined in ACF isolated in HID-AB-stained colon. Our previous work 7,31 and data presented here indicate that ACF identified in HID-AB colon and ACF as seen in MB-stained colon are strongly correlated. We found that ACF isolated in HID-AB, though to a lesser extent than MDF, have altered expression of b-catenin, in agreement with data on human ACF, 11 although some authors did not find alteration in b-catenin localization in rodent ACF.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…37 The localization of b-catenin was also determined in ACF isolated in HID-AB-stained colon. Our previous work 7,31 and data presented here indicate that ACF identified in HID-AB colon and ACF as seen in MB-stained colon are strongly correlated. We found that ACF isolated in HID-AB, though to a lesser extent than MDF, have altered expression of b-catenin, in agreement with data on human ACF, 11 although some authors did not find alteration in b-catenin localization in rodent ACF.…”
Section: Discussionsupporting
confidence: 67%
“…The method is similar to the HID-AB staining procedure that we 7,8 and others 9 use to identify MDF; this method only omits the preliminary staining of the colon with an high-iron diamine (HID) solution, a step that makes it possible to distinguish between sialomucin and sulfomucins production. 31 Although it is possible that Yoshimi's method will give satisfying results in the future, we think that more validation experiments should be performed before adopting it to identify MDF. In fact, a considerable fraction (about 24%) of the lesions identified as MDF by these authors turned out to be normal-like crypts at the histology.…”
Section: Discussionmentioning
confidence: 98%
“…However, the ACF studied had variable dimensions and included a certain number of lesions of larger size (11 ACF with 15 or more AC). We previously demonstrated (Caderni et al, 1995) that mild dysplastic characters (such as nuclear atypia, secretion of sialomucins and luminal alterations) are progressively increased during ACF growth. Similarly, Otori et al (1995) found a correlation between crypt multiplicity and dysplasia, although they also found large ACF with no signs of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The histological classification of ACF in both humans and experimental animals is a matter of debate (Bird et al, 1989;Bird and Pretlow, 1992;Caderni et al, 1995;Otori et al, 1995). In our study we did not evaluate the level of dysplasia in the ACF tested.…”
Section: Discussionmentioning
confidence: 99%
“…When PLU and PEG were directly compared, the number of ACF was smaller in PLU-fed than in PEG-fed rodents (Tables 2 and 3), but the difference was significant in mice only. In addition, PLU was more potent than PEG to decrease the number of large ACF, a better carcinogenesis endpoint than total ACF (Caderni et al, 1995). To summarize our previous rat studies, a 30-day PEG treatment decreases the ACF number 6-fold (median of 6 independent studies) Parnaud et al, 1999;Corpet et al, 2000).…”
Section: Discussionmentioning
confidence: 80%